Guarantee Instruments in International Development Finance: Factors, Dynamics and Prospects - Vladimir I. Bartenev (Финансовый журнал)
This paper examines the role of guarantee instruments in the modern system of international development finance and unveils the key factors affecting the dynamics and prospects of their use. The analysis shows that these instruments have existed for decades, but have gained prominence in the XXI century. Their recognition as indispensable tools for mitigating risks to private capital, particularly political risks, has been reflected in more mentions in milestone policy documents, organizational and intellectual efforts to revise statistical reporting rules and larger volumes of private finance mobilized. However, available OECD data show insufficient use of guarantees for development purposes, extreme disproportions in mobilized finance among providers (both bilateral and multilateral), beneficiary countries and sectors and a high portfolio heterogeneity. The prospects of the distribution of guarantees will be influenced by new statistical reporting principles and a number of powerful economic and noneconomic factors, such as: 1) a lack of progress on the Sustainable Development Goals; 2) worsening budgetary constraints in developed countries, hindering the increase in official development assistance; 3) intensifying geopolitical rivalries. A possible increase in the provision of development guarantees can only be welcomed. However, if it is accompanied by a reduction in funding for traditional aid programs affecting the fundamental factors of commercial and non-commercial risks, as well as prioritization of less vulnerable but more strategically important countries, the positive effect will fall short of expectations.